Challenges and Benefits of Inquiry-Based Learning in Physics - Bogador, Christine Joy; Camarao, Michael Kennedy G.; Matunding, Charlotte G.; Sombria, Khezel Jean F. (Future Science / FSH-PH Publications, 2024)
This qualitative research study investigates the experiences of Grade 12 STEM students in inquiry-based learning in physics at a private high school in Central Mindanao. The study aims to understand the challenges and benefits of this teaching approach, considering factors such as gender, academic performance, and prior exposure to inquiry-based learning (IBL). The study involved ten students who were selected through purposive sampling. The data were collected through one-on-one interviews. The findings reveal that the most challenging experience students faced in inquiry-based learning are problem-solving, lecture and laboratory activities, and theoretical concepts. Meanwhile, the benefits of IBL include collaborative learning, interactive discussions, and enhanced interest in learning. Most students preferred hands-on learning, while few preferred auditory and visual learning. The study suggests that development in IBL can be made based on students' challenges and learning styles, and the benefits that they can get from the approach in a supportive learning environment.